Eksplorasi Orientasi Kewirausahaan dan Orientasi Pasar terhadap Kinerja Usaha Berkelanjutan pada Usaha Mikro dan Kecil Agribisnis di Polewali Mandar - Halik, Rizky Ariesty Fachrysa; Fitri, Fitri; Arhim, Muhammad (Universitas Galuh, 2025)
This study aims to explore the influence of entrepreneurial orientation and market orientation on sustainable business performance in small and micro agribusinesses. The data used includes both primary and secondary data. Primary data was obtained through observations and interviews using questionnaires directed at micro and small agribusiness owners. Meanwhile, secondary data was sourced from previous research results, the development of micro and small enterprises through the Indonesian Central Bureau of Statistics (BPS), and other documentation sources. The sampling method used in this study was purposive sampling, with a minimum sample size of 45 business units. Partial Least Squares Structural Equation Modeling (PLS SEM) was employed to address the research objectives. The results show that entrepreneurial orientation significantly enhances sustainable business performance in agribusiness SMEs in Polewali Mandar. Agribusiness SME owners in Polewali Mandar exhibit attitudes and strategies to seize opportunities and face challenges in the market through innovation, proactivity, and risk-taking. Additionally, the market orientation variable significantly improves sustainable business performance in agribusiness SMEs in Polewali Mandar. The agribusiness SME owners in Polewali Mandar focus their activities on understanding and meeting customer needs and desires. They consistently monitor market trends, consumer behavior, and competitor actions to adapt with dynamic business environment.